PHILOSOPHY AS A SPIRITUAL PRACTICE: EDITORIAL (Analele Universității București.Filosofie, 2025)
Unprecedently in the entire human history, we live in a world of abundance of information, instantaneously accessible with a few clicks on our devices. What seemed to be in the past an exclusive privilege for a limited number of educated, is now taken for granted and open to everyone who has access to the Internet and programs of artificial intelligence.